SYSTEMATIC LITERATURE REVIEW: PENDEKATAN ETNOMATEMATIKA DALAM MATERI BANGUN RUANG TERHADAP KEMAMPUAN BERPIKIR GEOMETRIS SISWA - Mujtahidah, Siti Agustina; Mawarsari, Venissa Dian; Sulistyaningsih, Dwi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Geometric thinking ability is an essential competence in mathematics learning, particularly in solid geometry at the junior high school level. However, geometry learning that remains abstract often causes students to have difficulty in understanding concepts and developing spatial visualization skills. Therefore, a more contextual and meaningful approach is needed, one of which is ethnomathematics that integrates cultural elements into mathematics learning. This study aims to analyze the implementation of ethnomathematics in teaching solid geometry and its contribution to students’ geometric thinking ability. The study employed a Systematic Literature Review (SLR) method based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework. The analyzed articles were published between 2022 and 2026 and were obtained from Google Scholar, SINTA, Scopus, ERIC, DOAJ, and Garuda. Based on the selection process, 18 articles met the inclusion criteria. The results indicate that most studies report that the implementation of ethnomathematics in solid geometry learning provides more contextual learning experiences, which potentially improve students’ geometric thinking ability.